The effects of combined action of low-intensity electromagnetic radiation of the millimeter range and complexes of essential amino acids in tumor-bearing rats of old age - G. V. Zhukova; A. I. Shikhlyarova; L. N. Loginova; T. P. Protasova (Южно-Российский онкологический журнал, 2020)
Purpose of the study. Amplifying the effects of low-intensity modulated electromagnetic radiation (EMR) of the extremely high frequency range (EHF) on the tumor and adaptational status of old tumor-bearing rats with the help of complexes of essential amino acids enriched withvitamins and microelements (AaVM).Materials and methods. In experiments on 50 old white outbred male rats with transplantable sarcoma 45, the effects of EMR EHF and the combined effect of EMR EHF and AaVM were studied. For exposure to EHF EHF, the "Yav-1" medical device was used. The frequency modulation with 42.2 GHz as a center frequency was applayed. The duration of treatmaent was 4 weeks. We studied the dynamics of tumor size, adaptive status (according to hematological indicators of the character and tension of the general nonspecific adaptational reactions of the body), structural and functional changes in the tumor tissue, thymus and liver. In the statistical analysis of the results, student's t test and Wilcoxon-Mann-Whitney test were used.Results. The anti-stress effect of EMR EHF on the organism of old tumor-bearing rats, accompanied by temporary inhibition of sarcoma 45 growth was shown. The combination of EMR EHF exsposure and AaVM (as an additional metabolic factor) leaded to a persistent pronounced antitumor effect in 60% of animals. Inhibition of tumor growth in 4 times or more, as well as individual cases of its partial regression were observed. At the same time, a higher adaptational status including more numerous signs of activation of the thymus and liver than in the cases of using only EHF EMR were noted.Conclusion. The results indicate the promise of a combination of activation electromagnetic therapy and application of complexes of essential amino acids enriched with vitamins and microelements in the development of effective methods of accompanying and supportive treatment of cancer patients.